DISCIPLINE IN ISLAMIC RELIGIOUS EDUCATION: MAINTAINING TRUTH VALUES IN THE MODERN ERA - Yunus, Muhammad; M Mahbubi (LPPM STAI Muhammadiyah Probolinggo, 2026)
In the rapidly developing modern era, the main challenge in Islamic education is how to maintain the truth values taught in Islam, especially among the younger generation exposed to globalization, social media, and secular lifestyles. This study aims to analyze the role of discipline in Islamic Religious Education (IRE) at MTs Nurul Abror Asembakor Kraksaan Probolinggo in preserving Islamic values amid the progress of the times. This research uses a qualitative approach with a descriptive design, through semi-structured interviews, direct observations, and document analysis. Data were collected from 10 IRE teachers, 30 students, and 5 school administrators. The results of the study show that religious discipline is applied well within the school; however, the main challenge arises from the influence of social media and peer pressure outside the school. Furthermore, technology plays a dual role: on one hand, it can strengthen religious learning, but on the other hand, it also becomes a source of distraction. This study concludes that in order to preserve Islamic values, religious discipline needs to be applied consistently across all aspects of students' lives, both inside and outside school. The implications of this study suggest the need for synergy between schools, families, and communities in supporting Islamic education that is relevant to the challenges of the times. The recommendations of this study include the development of curricula and training programs that involve parents and the community in strengthening religious discipline among students.